Commissioning of the electromagnetic calorimeter ECAL of the HADES experiment. (October 2020) - Chudoba, P; Borisenko, D; Chlad, L; Galatyuk, T; Guber, F; Gumberidze, M; Kugler, A; Lalik, R; Morozov, S; Pechenov, V; Pethukov, O; Prozorov, A; et al.
Abstract: HADES (High Acceptance Di-Electron Spectrometer) is located at the GSI (Helmholtzzentrum für Schwerionenforschung) Darmstadt. It is an experiment focused on the study of the hot and dense nuclear matter mainly via the detection of the di-lepton pairs. Electromagnetic CALorimeter (ECAL) was recently added to the HADES setup. This new subdetector allows measuring of photons from the decay of neutral mesons and resonances. It also allows to discriminate between electrons and pions in the high-momenta region over 400 MeV/c. ECAL follows same hexagonal geometry as HADES, i.e. it consists of six sectors in azimuth. The first four sectors were finished and commissioned in 2018. The first experiment with ECAL included in HADES setup took place on March 2019, investigating the Ag+Ag reaction at beam energy of 1.65 A GeV. During the commissioning, several issues popped up and they were addressed. The issues and their solution will be described in the article.